The Crop Succession Systems Under No-Tillage Alters the Surface Layer Soil Carbon Stock and Stability - Paloma Pimentel de Souza; Deivid Lopes Machado; Micael Silva de Freitas; Aracy Camilla Tardin Pinheiro Bezerra; Tiara Moraes Guimarães; Eder Marcos da Silva; Natanael Moreira do Nascimento; Rafael da Silva Borges; Vladimir Eliodoro Costa; Claudio Hideo Martins da Costa; Simério Carlos Silva Cruz (Agriculture)
The main challenge of the no-tillage system (NTS) is to reconcile productivity, the maintenance of surface residues, and the stabilization of soil organic matter (SOM). To address this challenge, particularly in tropical regions, various cover crops have been tested. The objective of this study was to test the effects of agricultural crop succession systems on the stock and stability of soil organic carbon in different surface layers of the soils. The research was carried out in the state of Goiás, Brazil, in an experiment set up in 2016, designed in randomized blocks with a split-plot scheme (treatments and soil layers), comprising four repetitions (blocks). The treatments (plots) consisted of crops grown in succession to soybean, which were as follows: T1—soybean/corn (Zea mays); T2—soybean/pearl millet (Pennisetum glaucum); T3—soybean/Urochloa ruziziensis (brachiaria); and T4—corn + Urochloa ruziziensis. The subplots represented the following soil layers: 0–5, 5–10, 10–20, and 20–40 cm. We evaluated the biomass dry mass and the soil parameters such as soil density, total porosity, and light organic matter across all layers. The organic carbon, grain size fractionation (mineral-associated organic carbon—MOC; sand-sized carbon—POC), and isotopic composition (δ13C) were determined in the 0–5 and 5–10 cm layers. The highest biomass dry production was observed in the soybean/pearl millet succession, which reduced the soil density and increased the total porosity in the surface layer. The soybean/pearl millet treatment produced high amounts of light organic matter, particularly in the 0–5 cm layer, a result also found for the soybean/brachiaria and soybean/corn + brachiaria systems. The crop successions did not alter the soil carbon stock or stability; however, the surface layer stored the highest amount of carbon, with elevated total organic carbon values and carbon stocks and stability (MOC and POC). Overall, in this study, replacing corn with other crops in succession with soybean did not affect the stock or stability of soil organic carbon. The species grown in succession with soybean contributed to the higher surface carbon stock and stability, promoting the formation of more stable and recalcitrant carbon.